Awareness of coronary heart disease in rural areas of Mangalore - George, Grace Mariam; Badiger, Sanjeev; Kiran, K. G.; Kumar, Nanjesh (International Journal Of Community Medicine And Public Health, 2017)
Background: Coronary heart disease is the impairment of heart function due to inadequate blood flow to the heart, compared to its needs caused by obstruction. It is the cause of 25-30 percent of deaths in most industrialised countries. The WHO has drawn its fact that coronary heart disease is a modern epidemic .A steady decline in mortality is seen in western countries due to changes in lifestyles and related risk factors. Objectives of the study to assess the knowledge of the people regarding coronary heart disease, to identify who are at risk and to test their attitudes and practices. Methods: This is a descriptive study. The sample size was 256. The study was done among the OPD patients attending the rural health centres of a tertiary hospital in Mangalore. Time period was two months. Results: Our community based cross-sectional study demonstrated good knowledge (57.42%), good attitude but poor practice regarding the cardiovascular health in the rural population of Mangalore. Conclusions: There is a need for concerted efforts for health education (e.g. audio visual aids) focusing more on Coronary heart disease causations, signs and symptoms, and treatment facilities. Conducting screening camps aiming more towards cardiovascular check-up- including lipid profile, blood sugar, ECG in addition to routine check-up; preferably once in a year covering a mass population for the purpose of prevention and management is necessary.